2015
DOI: 10.4103/2279-042x.150051
|View full text |Cite
|
Sign up to set email alerts
|

Emergence agitation prevention in paediatric ambulatory surgery: A comparison between intranasal Dexmedetomidine and Clonidine

Abstract: Objective:Emergence agitation (EA), a short-lived, self-limiting phenomenon, arises frequently after the use of inhalational agents and hampers the implementation of pediatric ambulatory surgery in spite of using so many drugs with variable efficacy.Methods:In this prospective, double-blinded, parallel group study (2008–2009), 80 children of both sex aged 3–7 years, with American Society of Anesthesiologists (ASA) physical status grade I-II, undergoing sevoflurane-based general anesthesia for elective day care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…Eventually, 63 trials (19-81) including 7,714 patients were identified through our search strategy (Figure 1). All included trials were divided into nine groups based on control drugs: placebo , midazolam (19,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71), opioids (29,45,(72)(73)(74), propofol (or pentobarbital) (22,25,42,75,76), ketamine (26,60,(77)(78)(79), clonidine (80), chloral hydrate (81), melatonin (59), and ketofol (ketamine and propofol) (23). We assigned propofol and pentobarbital into the same group because both of them produced general anesthetic efficacy through directly activating the γ-aminobutyric acid A receptor of the central nervous system (82).…”
Section: Study Location and Selectionmentioning
confidence: 99%
“…Eventually, 63 trials (19-81) including 7,714 patients were identified through our search strategy (Figure 1). All included trials were divided into nine groups based on control drugs: placebo , midazolam (19,(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71), opioids (29,45,(72)(73)(74), propofol (or pentobarbital) (22,25,42,75,76), ketamine (26,60,(77)(78)(79), clonidine (80), chloral hydrate (81), melatonin (59), and ketofol (ketamine and propofol) (23). We assigned propofol and pentobarbital into the same group because both of them produced general anesthetic efficacy through directly activating the γ-aminobutyric acid A receptor of the central nervous system (82).…”
Section: Study Location and Selectionmentioning
confidence: 99%
“…Because of the particularity and arduous work of paediatric anaesthesia, it is necessary to administer premedication using drugs such as dexmedetomidine (DEX) or midazolam (MDZ) for sedation, analgesia, relief of the stress response, and elimination of nervousness, anxiety, and fear. DEX, a highly selective α 2 -receptor agonist with a ratio of affinity between α 2 and α 1 receptors 7.36 times higher that of clonidine, 5 is the most prevalent premedication used in paediatric anaesthesia because of its sedative, analgesic, amnesic, anxiolytic, and sympatholytic properties without respiratory depression. 6 Various studies have demonstrated that DEX more effectively decreases anxiety and sedation, reduces EA, and provides postoperative analgesia than does MDZ in children; 7 – 10 however, the definitive effects of DEX versus MDZ in paediatric anaesthesia with sevoflurane remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies suggested that Dex is safe in children. 3 5 , 10 , 19 22 Some showed that agitation and pain scores were significantly reduced by Dex, although the waking and extubation times were both significantly longer in children administered a single dose of Dex (0.5 µg/kg) 5 min after tonsillectomy 23 or in children given Dex 0.5 µg/kg/h intravenously after anesthesia induction. 24 Another randomized, controlled trial showed that a continuous infusion of Dex (0.2 µg/kg/h) after anesthesia induction could significantly reduce the frequency of ED by 10%–26%.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies suggested that dexmedetomidine (Dex) is safe in children. 3 5 With its hypnotic, analgesic, sedative, and anxiolytic effects, 6 it has been shown to improve intraoperative hemodynamic stability, minimize responses to stimuli, and reduce the need for other anesthetic agents. 7 Previous studies, however, have reported conflicting results on the effects of Dex on EA and ED.…”
Section: Introductionmentioning
confidence: 99%